Association beetween socio economic factor’s, nutritional intake and Incidence of anemia in Pregnant Women in District Wedi, Klaten Regency - Mariyana, Anna; Sandy Ulya, Pramitha (Journal of Advanced Nursing and Health Sciences, 2023)
Background: Anemia is caused by a lack of red blood cells to deliver oxygen to tissues and the fetus. Anemia can be detected if the Hb level is <11 mg. This study aims to determine the influence of socio-economic factors, nutritional intake and ANC visits on the incidence of anemia in pregnant women. Subject and method: The type of research is observational analytic with a case-control design. This research was conducted at the Wedi Community Health Center, Klaten Regency from January to February 2023. A sample of 100 pregnant women was selected using simple random sampling. The dependent variable is maternal anemia, the independent variables are maternal age, maternal parity, maternal education, family income, number of family members, food consumption patterns and ANC visits. Data collection techniques used questionnaires and were analyzed using logistic regression. Results: Pregnant women aged < 20 years increase the risk of anemia in pregnant women (b: 1.52; p= 0.178), parity of multigravida mothers increases the risk of anemia in pregnant women (b: 3.38; p= 0.011), maternal education <high ​​school increases the risk of maternal anemia pregnant (b: 2.15; p= 0.056), low family income < average increases the risk of anemia in pregnant women (b: 2.44; p= 0.035), number of family members > 4 increases the risk of anemia in pregnant women (b: 1.70; p= 0.121), non-diverse food consumption patterns increase the risk of anemia in pregnant women (b: 4.83; p=0.002), the number of ANC visits < 4 times increases the risk of anemia in pregnant women (b: 2.83; p=0.010).